Development of Traditional Parmayaman-Based Digital Flifbooks in Increasing Scientific Literacy in the Disruptive Era - Nirwana Anas; Ahmad Tarmizi Hasibuan (Jurnal Penelitian Pendidikan IPA, 2023)
The Covid 19 outbreak has reduced elementary age children's interest in reading, especially in the field of science. This becomes a problem, which makes education practitioners to make online learning interesting and fun. Digital Flipbook media is a "Patent" solution that is applied to children. One of the suitable learning materials to be made into Flipbook learning media is local Parmayaman. Local Parmayaman can also improve Science Literacy. This research uses an R&D approach with development steps. The product trials used in this study used a pre-experimental design with the one-group pretest-posttest method. The type of data used is qualitative and quantitative. The research results show that it has passed the validation of media experts, material experts, and scientific literacy instrument experts. Flipbook digital media based on local Parmayaman is valid and suitable for use as learning media after going through the improvement stage according to the suggestions and comments given by experts. Judging from the validation results of media experts by 94%, material expert validation results by 93%, and Science Literacy instrument experts by 93% and "valid and very feasible". Judging from the results of the main field trials on 43 students, it was obtained from the scores of students working on Science Literacy questions using the pretest and posttest. These values ​​are averaged and then N-gain is calculated. The calculation results obtained N-gain of 0.705. The N-gain score is included in the high category